2009
DOI: 10.1038/mt.2009.11
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Clustered Ligand Binding Into Nonviral Vectors: αvβ3 Targeting as an Example

Abstract: The development of techniques to efficiently deliver genes using nonviral approaches can broaden the application of gene delivery in medical applications without the safety concerns associated with viral vectors. Here, we designed a clustered integrin-binding platform to enhance the efficiency and targetability of nonviral gene transfer to HeLa cells with low and high densities of alpha(v)beta(3) integrin receptors. Arg-Gly-Asp (RGD) nanoclusters were formed using gold nanoparticles functionalized with RGD pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…However, a complete abolishment of transfection was not observed, suggesting that the carrier binds also through other nonspecific interactions with the cells. 42 CLSM observations further confirmed that attachment of the cRGD ligand greatly enhanced cellular internalization of the pDNA polyplex, compared with CDG2, in HUVECs that overexpress α v β 3 integrin (Figure 6), apparently through receptor-mediated endocytosis. Moreover, among the various cRGD-coupling carriers, CDG2-cRGD-5 was the most efficient carrier for delivering pDNA into HUVECs, which is in good agreement with the transfection activity of the optimal formulation.…”
Section: Discussionsupporting
confidence: 55%
“…However, a complete abolishment of transfection was not observed, suggesting that the carrier binds also through other nonspecific interactions with the cells. 42 CLSM observations further confirmed that attachment of the cRGD ligand greatly enhanced cellular internalization of the pDNA polyplex, compared with CDG2, in HUVECs that overexpress α v β 3 integrin (Figure 6), apparently through receptor-mediated endocytosis. Moreover, among the various cRGD-coupling carriers, CDG2-cRGD-5 was the most efficient carrier for delivering pDNA into HUVECs, which is in good agreement with the transfection activity of the optimal formulation.…”
Section: Discussionsupporting
confidence: 55%
“…The structure of viruses such as adenovirous type 2 and the surface density of their ligands have been studied to surmise the importance of multivalent ligands on binding efficiency 11 . Studies showed that penton-base proteins presented on adenovirus type 2 cover the surface of these viruses with regular spacing 11 . The surface density presented by this virus may substantially improve binding avidity to the cell receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The surface density presented by this virus may substantially improve binding avidity to the cell receptors. The simulation of the natural structure of viruses based on their ligand density has been utilized to engineer targeted clustered ligands 1112 . Studies showed that, the optimum distribution of ligands on the surface of viruses is a key factor for binding and cellular uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugation of folic acid with the aminomethacrylate-phosphoryl-choline based copolymer, allowed transfection of cells overexpressing the receptor for folic acid in some human tumors cells (Lam et al, 2009). A PEI-derived polyplex conjugated with an Arg-Gly-Asp peptide, which binds to the α v β 3 integrin receptor, resulted in efficient transfection of HeLa cells with low and high densities of α v β 3 integrin (Ng et al, 2009). As observed in viral vectors and lipoplexes, antibodies can be also conjugated with polyplexes to target genetic material to specific cell types.…”
Section: Polyplexesmentioning
confidence: 99%